2013
DOI: 10.1161/circheartfailure.113.000539
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Titin Hypophosphorylation Importantly Contributes to Heart Failure With Preserved Ejection Fraction in a Rat Metabolic Risk Model

Abstract: Background— Obesity and diabetes mellitus are important metabolic risk factors and frequent comorbidities in heart failure with preserved ejection fraction. They contribute to myocardial diastolic dysfunction (DD) through collagen deposition or titin modification. The relative importance for myocardial DD of collagen deposition and titin modification was investigated in obese, diabetic ZSF1 rats after heart failure with preserved ejection fraction development at 20 weeks. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
319
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 266 publications
(357 citation statements)
references
References 37 publications
33
319
1
4
Order By: Relevance
“…For instance, Kennedy et al (32) recently reviewed blood pressure responses in obese mouse models such as Lep ob/ob , LepR db/db , and HFD-induced obesity; responses of blood pressure include an increase, decrease, or no change, largely depending on strain, sex, age, environment, and the method of measuring BP. In this study, we did not observe an impact from HFD on the development of hypertension in either Con-HF or Dia-HF mice; our results are similar to reported observations in 5 out of 6 nephrectomized rats fed with HFD (33) and obese ZSF1 rats (34). Previously, the mild hypertension we noted in Dia-ND animals (9,10) was mainly because of renal hypertrophy related to renal hyperfiltration with increased GFR.…”
Section: Discussionsupporting
confidence: 90%
“…For instance, Kennedy et al (32) recently reviewed blood pressure responses in obese mouse models such as Lep ob/ob , LepR db/db , and HFD-induced obesity; responses of blood pressure include an increase, decrease, or no change, largely depending on strain, sex, age, environment, and the method of measuring BP. In this study, we did not observe an impact from HFD on the development of hypertension in either Con-HF or Dia-HF mice; our results are similar to reported observations in 5 out of 6 nephrectomized rats fed with HFD (33) and obese ZSF1 rats (34). Previously, the mild hypertension we noted in Dia-ND animals (9,10) was mainly because of renal hypertrophy related to renal hyperfiltration with increased GFR.…”
Section: Discussionsupporting
confidence: 90%
“…Increase in PEVK element phosphorylation (Ser-12742 in the rat sequence) was 31% in human HTN (45) and 23% in patients with dilated cardiomyopathy (26), being similar to the 32.6% in mRen2 rats as reported here. A more prominent change (ϳ70% decrease) in PEVK phosphorylation level was found in a different site within the PEVK region of titin (Ser-12884) in a metabolic model of HFpEF (19). Moreover, hypophosphorylation of N2-Bus residues was also noted previously, accompanying PEVK hyperphosphorylation (45).…”
Section: Sd Mren2supporting
confidence: 64%
“…Phospho-specific antibodies were developed against Ser-11878 (PS26; GL Biochem, Shanghai, China; 1:1,000) and Ser-12022 (PS170; Genscript, Piscataway, NJ; 1:1,000) in the full human sequence. These human Ser-11878 and Ser-12022 phospho-sites correspond to Ser-12742 and Ser-12884 in the rat genome, respectively (19). Finally, peroxidase-labeled secondary antibody (anti-rabbit-POD; from Sigma-Aldrich; 1:40,000) and enhanced chemiluminescence reaction (ECL) were used for detection.…”
Section: Methodsmentioning
confidence: 99%
“…No differences in titin-isoform ratio, compared with healthy hearts, were seen in (1) ; and (5) hearts of a metabolic risk-induced HFpEF model with hypertension and diabetes mellitus, the Zucker spontaneously hypertensive fatty 1 diabetic rat (lean or obese). 125 In conclusion, titin-isoform transitions add to the modification of total myocardial passive stiffness in heart development and presumably in a subset of patients with HF. The titin-isoform shift can go in different directions in different types or stages of heart disease.…”
Section: Adjustment Of Titin Stiffness By Isoform Switching In Nonfaimentioning
confidence: 96%
“…140 Other studies have since demonstrated hypo-phosphorylation of total-titin in human HCM 123 and in animal models of HFpEF. 117,125 A few studies have reported an increased ratio of phospho-N2BA:phospho-N2B in human HF, including HFpEF, aortic stenosis, and HFrEF. 111,112 However, as the N2BA:N2B isoform-expression ratio was also increased in these patient hearts, the proportion of phospho-titin to all-titin (per isoform) may have been similar in the nonfailing and failing hearts.…”
Section: Altered Titin Phosphorylation In Hf and Implications For Diamentioning
confidence: 99%